Democratizing Texas Politics : Race, Identity, and Mexican American Empowerment, 1945-2002 - Marquez, Benjamin, 1953- (Book collections on Project MUSE., 2014)
"In 1940 there were virtually no Mexican American elected officials in Texas at any level of government. By the turn of the century that was no longer true. In fact, Mexican Americans in Texas had effectively reached parity with their white counterparts in elected office. This book tells the story of this dramatic transition in Texas politics and seeks to explain it utilizing original archival research, hours of interviews with leading figures, and the collected letters of some of Texas' most important politicians and activists. The departure from a racially uniform political class in Texas to incorporate Mexican Americans was slow and difficult. Mexican Americans rarely won easy victories and the concessions they received were often yielded with reluctance. Threatened with racial tension, minority status and political exclusion, it is perhaps surprising that Mexican Americans were so successfully incorporated. I argue that their incorporation was the culmination of six interrelated political processes: the long history of political organization among Mexican Americans in Texas that had established an effective corps of leaders, an increasing proportion of the voting-age population, new Democratic Party policies developed to increase the representation of women and minorities, a reinvigorated Republican Party that absorbed conservative voters and weakened resistance to racial reform in the Democratic Party, the civil rights legislation of the 1960s, and finally, an alliance with Anglo liberals that facilitated the transition to a more representative two-party system in Texas"--